One-pot production of ceria nanosheet-supported PtNi alloy nanodendrites with high catalytic performance toward methanol oxidation and oxygen reduction. Issue 48 (27th November 2020) - Kwon, Yongmin; Kim, Yena; Hong, Jong Wook; Whang, Youngjoo; Kim, Sujung; Wi, Dae Han; Byon, Hye Ryung; Han, Sang Woo
Abstract : The production of high-performance electrocatalysts consisting of intimately coupled PtNi nanodendrites and ceria nanosheets was realized by a one-pot method. Abstract : Devising efficient routes to realize hybrid materials consisting of intimately coupled metal nanocatalysts and nonstoichiometric metal oxides with finely controlled configurations is highly desirable to develop advanced fuel cell catalysts. Here, we report a facile one-pot synthesis strategy for the formation of closely coupled metal (PtNi alloy)–metal oxide (CeO x, ceria) hybrid nanostructures. Heating an oleylamine/oleic acid solution of mixed metal (Pt, Ni, and Ce) precursors yielded well-defined PtNi/ceria hybrids, in which PtNi alloy nanodendrites with multiple branches are well dispersed on small-grained ceria nanosheets. Due to their small grain size, the ceria nanosheets in the hybrids contain abundant oxygen vacancies and have high conductivity. The prepared PtNi/ceria hybrids exhibited outstanding electrocatalytic activity and stability toward both methanol oxidation and oxygen reduction reactions in comparison to their carbon-supported counterparts and a commercial catalyst, which can be attributed to the synergistic effects of the Ni component and ceria on the enhancement of the electrocatalytic function. The current strategy will find use in the design of optimal multicomponent catalysts for target reactions.